The Distortion of Market Prices in Islamic Microeconomic - Achmad Fadlil Abidillah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This paper aims to describe how market price distortions are seen in Islamic microeconomics. The method used in this research is a qualitative method. The data comes from documents in the form of books, journals, and other scientific writings. This paper contains several findings regarding some price distortions that can occur in the market such as supply-demand manipulation (bai' najasy, ikhtikar, and talaqqi rukban), tadlis or fraud, and taghrir or uncertainty.